The electrophysiological assessment of visual function in Multiple Sclerosis - Joshua L. Barton; Justin Y. Garber; Alexander Klistorner; Michael H. Barnett (Clinical Neurophysiology Practice, 2019)
The assessment of vision is integral to the diagnosis and monitoring of patients with multiple sclerosis (MS). Visual electrophysiology, previously a critical investigation in patients with suspected MS, has in large part been supplanted by magnetic resonance imaging in clinical routine. However, the development of multi-focal visual evoked potentials and the advent of putative re-myelinating therapies that can be monitored with these techniques has led to a resurgence of interest in the field. Here, we review the clinical applications, technical considerations and limitations of visual evoked potentials in the management of patients with MS. Keywords: Multiple sclerosis, Visual evoked potentials, Multifocal visual evoked potentials